Formulasi Mikrokapsul Ranitidin HCl Menggunakan Rancangan Faktorial dengan Penyalut Etil Selulosa - Lili Fitriani; Ulfi Rahmi; Elfi Sahlan Ben (Jurnal Sains Farmasi & Klinis, 2014)
Ranitidine HCl is a histamine H2-antagonist which is used in the treatment of benign gastric and duodenal ulceration. In order to improve its bioavailability and half life time, microcapsule is prepared to extend the dose regiment. The aim of this study was to formulate and optimize ranitidine HCl containing microcapsule to prepare a suitable sustained release delivery system using factorial design. Microspheres were prepared using ethylcellulose by solvent evaporation method. The effect of different formulation variables, including stabilizer concentration (1-2 %) and drug/polymer ratio (2:2-1:2) on appearance, and entrapment efficiency was investigated. Data analysis showed that microspheres with optimum entrapment efficiency could be prepared using 2 % span 80, and 1:2 drug/polymer ratio. The results showed spherical shaped microcapsules, and porous, with realeasing time up to 10,55 hours.